A Simulation Study on the Spatial-Temporal Characteristics of Pore Water Pressure and Roof Water Inrush in an Aquiclude - Tao Yang; Ji Li; Longwen Wan; Sheng Wang (Shock and Vibration)
As the working face advances, the overlying aquiclude is subjected to periodic dynamic loads, causing pore water pressure distortion, which provides important forewarning for a water inrush disaster in shallow coal seams. In order to analyze the pore water pressure in an aquiclude and determine the spatial-temporal characteristics of the water inrush, the aquiclude is simplified into a saturated, porous, liquid-solid medium and a viscoelastic dynamic model is created to obtain the analytical solution of the pressure distribution. FLAC3D is used to develop a fluid-solid coupling model and to analyze the characteristics of the pressure change and overburden under different mining intensities. This study on pore water pressure in an aquiclude and the determination of the spatial-temporal characteristics of the water inrush provides a foundation for developing early-warning systems for roof water inrush.